Effect of oxalic acid on Ca2+ concentration and signaling pathways in plants - Li Yang; Zhao Yuan; Xu Youping; Wang Jipeng; Cai Xinzhong (浙江大学学报. 农业与生命科学版)
Sclerotinia sclerotiorum (Lib.) de Bary is one of the most important necrotrophic fungal pathogens. It has a very wide host range, reportedly infecting over 400 species of plants worldwide. S. sclerotiorum causes white mould (stem rot) disease of many important crops, especially oil crops such as rape, soybean, peanut and sunflower. However, so far, the molecular mechanism of pathogenicity of this pathogen has not been fully understood. It is clear that cell wall degrading enzymes (CWDEs) and oxalic acid (OA) are the important pathogenicity factors of S. sclerotiorum. During infection, the pathogen secretes CWDEs to degrade components of host plant cell wall and thus facilitates its infection. OA is of concern as another essential pathogenicity factor. The known roles of OA in pathogenicity include lowering extracellular pH value and thus increasing activity of CWDEs, altering redox status to regulate accumulation of reactive oxygen species (ROS) and programmed cell death (PCD), and having direct toxicity to plant cells. Additionally, OA is thought to be able to chelate calcium in cell wall and thus enhances its degradation by some CWDEs secreted by the pathogen. However, the effect of OA on Ca2+ concentration of the whole cells and Ca2+ signaling pathways remains unclear, which is examined in this study.The dye Fluo-4 interacts with Ca2+ inside living cells and can be detected with the green fluorescence by confocal laser-scanning microscope. Employing Fluo-4 as an indicator of Ca2+ concentration inside cells, the effect of OA on Ca2+ concentration was analyzed. Infiltration of 1 mmol/L OA only weakly lowered the Ca2+ concentration inside leaf cells of Arabidopsis. However, 10 mmol/L OA rapidly and dramatically reduced it. The fluorescent signal was almost undetectable since 10 min post this treatment. This result reveals that the effect of OA on Ca2+ concentration inside plant cells is dependent on their concentrations.Additionally, the effect of OA on gene expression of Ca2+ signaling pathways was examined using real-time quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). The genes under investigation included CRT gene family, which play roles in regulation of Ca2+ homeostasis and signaling and disease resistance, two CDPKs, which are Ca2+ sensors, and CAMTA3, a calmodulin-binding transcriptional factor involved in regulation of plant disease resistance. Expression results showed that the tested genes responded differently to OA treatment. Generally speaking, the expression of two CDPKs and CAMTA3 altered more strongly but in contrast direction in response to OA in comparison with CRT family genes. In addition, these genes were expressed differently in response to OA of different concentrations. The expression level of these genes was much higher in response to OA of higher concentration. In response to 1 mmol/L OA, the expression of three CRT genes and CDPK1 was continuously up-regulated by about 10 times for CRT3 and 130 times for CDPK1 at 24 h post treatment (hpt), and the expression of CAMTA3 gene was continuously down-regulated to be almost undetectable at 24 hpt, while the expression of CDPK2 gene was significantly up-regulated at 6 hpt and then slightly reduced at 24 hpt.In summary, the data of this study reveal that 10 mmol/L OA, which is typically secreted by S. sclerotiorum during infection, rapidly and dramatically reduces Ca2+ concentration inside plant cells. OA may target Ca2+ signaling pathway at some key components such as CRTs, CDPKs and CAMTA3 during plant and S. sclerotiorum interactions.